Not Necessarily Existential Threats: Identity-Constitutive Role of the Foreign Policy Discourse on Distant Humanitarian Crises - Erdem Ceydilek (Alternatif Politika)
The depiction of identity in foreign policy analysis is typically presented as inherent or predetermined. However, discursive approaches within the field, particularly poststructuralism, have emphasized foreign policy discourse's influence on identity formation. The main aim of this paper is to elucidate the performative relationship between identity and foreign policy through a poststructuralist lens, even in situations that are not existential or geographically proximate crises. This study employs a critical discourse analysis methodology to examine the performative dynamics between foreign policy discourse by the Justice and Development Party (AKP) policymakers and officials from the Ministry of Foreign Affairs (MFA) about distant natural disasters and the construction of the Turkish national identity. The study presents three primary findings: firstly, the AKP's foreign policy discourse recognizes the Indonesia and Pakistan disasters as significant events, in contrast to the case of Haiti; secondly, this discourse constructs a homogenous Turkish identity; and thirdly, this homogeneous Turkish identity qualifies by several signifiers and is distinguished from external others.